2013
DOI: 10.1063/1.4798584
|View full text |Cite
|
Sign up to set email alerts
|

Dexterous manipulation of microparticles using Bessel-function acoustic pressure fields

Abstract: We show that Bessel-function acoustic pressure fields can be used to trap and controllably position microparticles. A circular, 16-element ultrasound array generates and manipulates an acoustic field within a chamber, trapping microparticles and agglomerates. Changes in the phase of the sinusoidal signals applied to the array elements result in the movement of the Bessel-function pressure field and hence the microparticles. This demonstrates ultrasonic manipulation analogous to holographic optical tweezers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(90 citation statements)
references
References 39 publications
1
87
0
Order By: Relevance
“…It has been demonstrated that transducer arrays can be used to generate acoustic vortices in fluid-filled chambers [10,[31][32][33]. By controlling the amplitude and phase of each transducer in a circular array, one can generate approximate Bessel-function pressure fields of the form [31]p…”
Section: Bessel-function Acoustic Vortex Fieldsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that transducer arrays can be used to generate acoustic vortices in fluid-filled chambers [10,[31][32][33]. By controlling the amplitude and phase of each transducer in a circular array, one can generate approximate Bessel-function pressure fields of the form [31]p…”
Section: Bessel-function Acoustic Vortex Fieldsmentioning
confidence: 99%
“…It is inspired by, and closely resembles, the experimental systems in Refs. [9,10,[30][31][32]. The radius of these chambers is typically around 1 mm, and the chambers may have between 8 and 64 transducer elements operating at MHz frequency.…”
Section: Model Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent improvements to standing acoustic wave schemes led to levitating and translating single or multiple particles in air [15], and acoustophoresis provides advanced particle, cell and organism separation in complex microfluidic environments [16,17]. Standing wave schemes have recently been proposed to accurately manipulate particles in two dimensions using surface [18,19] or bulk acoustic waves [20] with phase or frequency shifts in order to demonstrate capabilities similar to OTs. However, all the aforementioned techniques share the same limitations; e.g., standing waves form multiple equilibrium positions in one or two dimensions, each of which is likely to trap one or various particles at the same time, therefore precluding separability and selectivity at the single particle level with ease [21,22].…”
mentioning
confidence: 99%